Modern Diagnosis and Treatment of Chronic Colostasis in Children - U.Sh, Mamajonov; B.Kh, Mirzakarimov; B.B, Toshpulatov; M.A, Yuldashev; D.K, Karimov; U.A, Khusanboeva (Journal of Neonatal Surgery, 2025)
As a result of a comprehensive follow-up of 220 children with colostasis (aged 8 months to 14 years), organic (Hirschsprung's disease -20%) and functional (megarectum -45.8%; megarectum megacolonoma 21.7%; dolichosigma 12.5%) etiology of the disease were revealed. Surgical methods of treatment were used in organic etiology, while various methods of conservative treatment were used in functional diseases